Pengaruh Kinerja Keuangan, Ukuran dan Umur Perusahaan Terhadap Nilai Perusahaan dengan Pengungkapan Corporate Social Responsibility (CSR) Sebagai Variabel Moderasi - Novianti, Elviana; Rina Asmeri; Dica Lady Silvera (Ekasakti Pareso Jurnal Akuntansi, 2023)
This research aims to examine the influence of financial performance, company size, and age on company value with corporate social responsibility (CSR) disclosure. The dependent variable in this research is Company Value with Corporate Social Responsibility (CSR) Disclosure. Meanwhile, the independent variables are Financial Performance, Company Size, and Age. The population in this study were manufacturing companies listed on the Indonesian Stock Exchange for the 2016 - 2020 period. The sampling method used was purposive so 7 samples were obtained. The total amount of data processed in this research was 35 data. The type of data used is secondary data. The data analysis method used in this research is multiple regression. The results of this research indicate that financial performance has a significant effect on company value. Meanwhile, company size and age do not significantly affect company value.